A critical theory of politics: Grounds, method and aims. Reply to Simone Chambers, Stephen White and Lea Ypi. (March 2015) - Forst, Rainer
In this article, I address the various objections raised by Simone Chambers, Stephen White and Lea Ypi concerning my version of a critical theory of politics. I explain the basic assumptions that inform my account of a critique of relations of justification, its particular method and aims.